Studying the Improvement of the Solubility of Cellulosic Fibers (Journal of Engineering, 2017)
This study focuses for improving the increase the solubility of fiber cellulose in sodium hydroxide solution in concentrations ranging from (4- 12%), from one point of view and from other point of view in (sodium hydroxide and urea) solution concentration (6% NaOH + 4% urea), under  low temperature (- 15, - 20 Co) , depending on the principle of  reducing the degree of polymerization for  fiber cellulose, which is represented in our tests cotton linter who its represent  (Whatman filter paper, Grade 1), some samples subjected to chemical pretreatment as simulation the method of decomposition of cellulosic materials by white or brown fungi that grow on trees, this method involves the use of chemical materials, including hydrogen peroxide (H2O2) , oxalic acid C2H2O4 and ferrous sulfate FeSO4 to be reaction known ( Fenton reaction or Fenton's reagent) which produce  free radicals helps the decomposition of cellulose fibers. The results were as follows: The solubility of cellulose fiber in sodium hydroxide solution was up to 42% cellulose and the best sodium hydroxide concentration is 8% for treated simples in Fenton solution and for untreated simples were the best solubility of cellulose fiber up to 28% and the best temperature is -20 Co for both. For the solubility of  cellulose fibers in sodium hydroxide and urea solution (6% NaOH + 4% urea)  was more than 60% of treated cellulose in Fenton reaction , while for untreated cellulose was the best solubility ratio up to 35% and it was the best temperature - 15 Co